The Conceptualization of Femininity in Rio de Janeiro's Popular Music: Samba and Funk - Costa, Laura da (2024)
This study aims to understand the conceptualization of the feminine in the musical genres of funk and samba from the city of Rio in the perspective of Conceptual Metaphor Theory (CMT) (LAKOFF; JOHNSON, 2002 [1980]). The study was based on the analysis of two hundred (200) songs from both musical genres in Rio de Janeiro, divided equally - one hundred songs for each genre. The songs mentioned, in the context of funk, were released to the public between 2017 and 2021, by the artists Anitta, Dennis DJ, Lexa, Ludmilla, and Pocah, all born in the state capital of Rio de Janeiro. On the samba side, 100 songs were also collected, this time released between 2018 and 2022, written by Dudu Nobre, Mart'nália, Mumuzinho, Dilsinho and Martinho da Vila. A qualitative-quantitative methodological approach was used to analyze the lexicon, with interpretative aspects and the use of AntConc software to check the frequency of specific terms. In terms of the data related to funk carioca, the lexicon related to female body parts was relevant, especially “butt”, which had an average of 13.56 occurrences. On the other hand, samba carioca showed marked differences from funk songs in terms of gender representation, the presence of body parts and the use of conceptual metaphors. A significant frequency of occurrences of the word "heart" was observed in the context of the samba. In addition, the recurrence of elements of nature, such as water, sun, day and flowers, was identified, as licensed by conceptual metaphors structuring meanings relating to love themes and descriptions of female individuals. In short, this study demonstrates the metaphorical and metonymic divergences of both Rio musical genres, and the implication of such occurrences with the Rio social context and its reading of the WOMAN category.